Religious Secularism: Muslim Perception and the Effects of France and Belgium's Niqab and Burqa Prohibition - Syah, Yoshy Hendra Hardiyan; Shamsu, Lilly Suzana binti Haji; Kuswana, Dadang (Jurnal Iman dan Spiritualitas, 2024)
This article examines how the Muslim community perceives religious secularism in France and Belgium. Second, to explore the negative and positive impacts of the niqab and burqa ban policy on the perception of the Muslim community in France and Belgium. This article uses a descriptive qualitative research method (Field Research) with a participatory approach. Namely, the researcher conducted direct observations in France (Cannes, Marseille, and Dunkerque) and Belgium (Saint-Nicolas and Bouge) on 19-26 February 2022. The data collection techniques in this article are primary data and secondary data. Preliminary data includes field observations, interviews, and documentation. Meanwhile, secondary data includes books, scientific articles, and popular articles still relevant to this research. Then, the researcher conducted semi-structured interviews with informants or sources, namely Muslim women in Belgium and France. Furthermore, the documentation technique uses a theoretical reference source referring to Stephen P. Robbins' version of perception theory. The findings in this article are the perceptions of the Muslim community, which has been known above. The views of the Muslim community in France and Belgium towards religious secularism in terms of the prohibition of wearing the Niqab and Burqa vary greatly. These very varied views or perceptions are influenced by the principles, experiences, knowledge, attitudes, social conditions, surrounding environment, and personalities of those (Muslim communities) who live in France and Belgium. The negative impacts are more dominant, and this may worsen the social and economic conditions of Muslim communities.